Changes in vitamin content and sensory characteristics of frozen wild berries during storage - Simahina, Galina; Naumenko, Nataliia; Kaminska (Halapsina), Svitlana (My University, 2024)
The aim of the study was to evaluate changes in the content of ascorbic acid, bioflavonoids, and β-carotene, as well as the organoleptic properties of frozen wild berries under the influence of cryoprotectants after long-term storage. Berries, processed with a water solution of cryoprotectant before freezing, after 9 months of storage, showed almost no significant difference with fresh raw materials in terms of vitamin content and sensory characteristics. The optimal conditions for defrosting of berries was temperature 0 °C for 30–33 minutes.

Метою роботи було оцінити зміни вмісту аскорбінової кислоти, біофлавоноїдів і β-каротину, а також органолептичних властивостей заморожених лісових ягід під впливом кріопротекторів після тривалого зберігання. Ягоди, оброблені перед заморожуванням водним розчином кріопротектора, після 9 місяців зберігання за вмістом вітамінів і сенсорними показниками практично не відрізнялися від свіжої сировини. Оптимальні умови для розморожування ягід відбувалося при температурі 0 °С протягом 30–33 хв.
Keywords: кафедра технології оздоровчих продуктів; кафедра іноземних мов професійного спрямування; wild berries; freezing; defrosting; vitamins; sensory; лісові ягоди; заморожування; розморожування; вітаміни